ANALISIS YURIDIS PRAKTIK MONOPOLI DALAM JASA PENGURUSAN TRANSPORTASI PENGIRIMAN (EKSPOR) BENIH BENING LOBSTER BERDASARKAN UU NOMOR 5 TAHUN 1999 (STUDI TERHADAP PUTUSAN KPPU NOMOR 04/KPPU- I/2021): Juridical Analysis of Monopoly Practices in Services Shipping Export Lobster Seeds Based on Law Number 5 of 1999 (Study of KPPU Decisions Number 04/KPPU-I/2021) - Andrina, Bidhari; Anggraini, Anna Maria Tri (Faculty of Law, Universitas Trisakti, 2024)
Fishery products are one of the main livelihoods of the Indonesian people which can be traded internationally. To facilitate international trade, sending products to international shipping areas from Republic of Indonesia (export) can be done by appointing a transportation management service company. This is done to avoid monopolistic practices carried out by each business actor to benefit themselves. However, implementing these regulations is certainly not easy. One of the cases is the alleged violation of Article 17 of Law 5/1999 committed by PT Aero Citra Kargo (PT ACK). In this case, the author conducts a discussion related to monopoly practices in BBL delivery (export) transportation services by PT ACK according to Article 17 and the accuracy of KPPU decision No. 4/KPPU-I/2021 regarding monopolistic practices for BBL delivery (export) transportation services against PT ACK. Next, the author analyzes the fulfillment of the legal elements and approaches to Article 17 of Law 5/1999. On the other hand, the author also discusses the active role of the government, the period of substitution, and the absence of sanctions against violators in this decision to see the accuracy of the decision. So the conclusion of this research shows that PT ACK has violated Article 17, however in the decision there are still many things that are not explained further, especially regarding the absence of sanctions against violators.